TRANSFORMATION IDEAS OF ACTIVE APPROACH IN TEACHING HERITAGE ELEONOR YANOVSKA - Sіchkar Alla D. (Educological discourse, 2014)
The article connects to the problem of formation ideas active approach in Ukrainian preschooling at the beginning of the XX century, their development and transformation under the influence of socio-political ideology. According to the results of theoretical analysis of scientific achievements of the Soviet period and the period of independent Ukraine summarized Eleonory Yanovska contribution to the theory, practice active approach to training and education of preschool children. Allocated productive ideas activity approach to adapt them to modern educational space.